2010
DOI: 10.1128/mcb.01215-09
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor TCFAP2C/AP-2γ Cooperates with CDX2 To Maintain Trophectoderm Formation

Abstract: In mammals, cell lineage specification is established at the blastocyst stage. At this stage, transcription factor Cdx2 represses pluripotency genes, thus promoting extraembryonic trophoblast fate. Recently, transcription factor Gata3 was shown to act in a parallel pathway in promoting trophoblast cell fate, suggesting that there are more factors working in the trophoblast lineage. Here, we report that the transcription factor Tcfap2c is expressed at a high level in the trophectoderm and is able to induce trop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
157
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(177 citation statements)
references
References 40 publications
16
157
1
Order By: Relevance
“…These studies have revealed a number of TFs that are essential to establish and maintain TSCs, including Eomes, Elf5, and Tfap2c (Russ et al 2000;Donnison et al 2005;Kuckenberg et al 2010). Here, we show that these same three TFs physically bind to each other to form multimeric TF complexes and co-occupy trophoblast genes, including themselves, driving their expression.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…These studies have revealed a number of TFs that are essential to establish and maintain TSCs, including Eomes, Elf5, and Tfap2c (Russ et al 2000;Donnison et al 2005;Kuckenberg et al 2010). Here, we show that these same three TFs physically bind to each other to form multimeric TF complexes and co-occupy trophoblast genes, including themselves, driving their expression.…”
Section: Discussionmentioning
confidence: 83%
“…For instance, Cdx2 and Elf5 are coexpressed in TSCs, but, upon induction of differentiation, Cdx2 is down-regulated more rapidly than Elf5 (Ng et al 2008). Similarly in vivo, Cdx2 and Eomes are restricted to a narrow region of the ExE immediately overlying the epiblast, whereas Elf5 and Tfap2c have a much broader expression domain extending into the proximal ExE and ectoplacental cone (EPC) (Auman et al 2002;Ng et al 2008;Ralston and Rossant 2008;Kuckenberg et al 2010;Adachi et al 2013). These data point to a seeming discrepancy: Although core TFs are coexpressed and can mutually activate each other in the TSC compartment, their expression domains become divergent with the onset of differentiation.…”
mentioning
confidence: 99%
“…At this stage, Tead4 activates the expression of the transcription factors Cdx2 and Gata3 that are required for the establishment of a functional TE (Yagi et al 2007, Nishioka et al 2008, Home et al 2009, Ralston et al 2010. Cdx2 activates Gata3 and transcription factor Tcfap2c (and vice versa), which in turn represses the pluripotency genes, Nanog and/or Pou5f1 expression, leading to lineage restricted gene expression profiles (Niwa et al 2005, Home et al 2009, Kuckenberg et al 2010. Poor expression of all the above genes in cytoplasmic hybrids may have adversely affected ICM and TE lineage segregation.…”
Section: Discussionmentioning
confidence: 99%
“…AP2γ is expressed in the inner cell mass (ICM) and trophectoderm of mouse embryo [32,47], and previous studies have focused on its functions in extraembryonic development. However, the functions of AP2γ during development from ICM to neural/epidermal ectoderm are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…AP2α also regulates neural border specification during the neuralization stage in Xenopus and lamprey [30,31]. Mouse AP2γ is expressed in both extraembryonic and embryonic tissues [32,33] and displays multiple functions in extraembryonic development, neural crest induction and terminal epidermal differentiation [26,34,35]. Moreover, disruption of AP2γ leads to mouse embryonic lethality at approximately E7.…”
Section: Introductionmentioning
confidence: 99%